2013
DOI: 10.3389/fnhum.2013.00347
|View full text |Cite
|
Sign up to set email alerts
|

The influence of chronotype on making music: circadian fluctuations in pianists' fine motor skills

Abstract: Making music on a professional level requires a maximum of sensorimotor precision. Chronotype-dependent fluctuations of sensorimotor precision in the course of the day may prove a challenge for musicians because public performances or recordings are usually scheduled at fixed times of the day. We investigated pianists' sensorimotor timing precision in a scale playing task performed in the morning and in the evening. Participants' chronotype was established through the Munich Chrono-Type Questionnaire, where mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 33 publications
3
15
0
Order By: Relevance
“…The largest difference in SPR and variability of performances was between 09 and 21 h, similar to previous findings on spontaneous motor rates of tapping (Dosseville et al, 2002) and cycling (Moussay et al, 2002), which have shown slowest rates in the morning and fastest rates in the evening. These results suggest that melody performances increased in tempo and in temporal regularity from the morning to the evening, a finding that is somewhat consistent with a sample of largely night-owl chronotypes (Van Vugt et al, 2013). Participants completed all testing sessions in the same order in this study (to control for sleep differences between testing sessions); therefore, it is possible that some changes in melody performance rate and temporal variability were attributable to practice effects over the session trials.…”
Section: Discussionsupporting
confidence: 77%
“…The largest difference in SPR and variability of performances was between 09 and 21 h, similar to previous findings on spontaneous motor rates of tapping (Dosseville et al, 2002) and cycling (Moussay et al, 2002), which have shown slowest rates in the morning and fastest rates in the evening. These results suggest that melody performances increased in tempo and in temporal regularity from the morning to the evening, a finding that is somewhat consistent with a sample of largely night-owl chronotypes (Van Vugt et al, 2013). Participants completed all testing sessions in the same order in this study (to control for sleep differences between testing sessions); therefore, it is possible that some changes in melody performance rate and temporal variability were attributable to practice effects over the session trials.…”
Section: Discussionsupporting
confidence: 77%
“…The latter denote more variant behavior during the day rather than the weekday and week for both groups. In fact, intra-day variations of controls' fine-motor skills have been previously reported (Van Vugt et al, 2013) to be affected by the circadian rhythm, which can also be considered as a factor that might influence the findings here, due to its relation with fine motor movements during smartphone interaction. Also, dopamine plays a substantial role on circadian regulation and timing behavior (Agostino et al, 2011), whereas recent works (Videnovic and Golombek, 2017) present increasing evidence to disruption of circadian function in PD, where a dopamine-based therapy may increase the circadian oscillations.…”
Section: Discussionmentioning
confidence: 74%
“…There is a substantial body of literature exploring the association of chronotype, or diurnal preference, with human behavior and performance, with strong effects seen particularly in situations involving complex cognitive processing and executive function 9 10 11 . These studies report significant time of day effects on behavior due to multiple factors: age-related developmental changes from adolescence to adulthood 12 13 14 , significant behavioral differences between extreme chronotypes (larks and owls) 15 16 17 18 , and the difficulties people have in adapting their behavior to shifts in circadian timing 19 20 21 22 . The most widely used method for measuring chronotype in these studies is the Morningness-Eveningness Questionnaire (MEQ), designed by Horne and Östberg 23 .…”
mentioning
confidence: 99%